NARSKCA: Novel and robust symmetric key cryptography algorithm - Maram, Balajee; Kumar, Y Ramesh; Rao, K Lakshmana (International Journal of Scientific World, 2015)
In this research paper, a novel and strong symmetric key cryptography algorithm is proposed. NARSKCA is based on several symmetric cryptographic algorithms. NARSKCA is very simple that uses character converting algorithm, Fibonacci Number Series, Lucas Number series and bitwise XOR. In NARSKCA, 32 files are shared-secret files plays a vital role in this Proposed Algorithm. The Sub-keys are generated from those 32 shared-secret files which are useful in different rounds of Encryption and Decryption Process. The most important feature is the calculation of the final key from the Sub-Keys for each Text-Block. Key Generation, encryption/decryption schemes of NARSKCA are fast and difficult to predict by Cryptanalysts.